Data analysis of the FIC detector at the n_TOF facility - Karadimos, D.; Ioannides, K.; Assimakopoulos, P.; Tsagas, N.; Paulopoulos, P.; Vlahoudis, V.; Cennini, P.; Ketlerov, V.; Konovalov, V.; Stamoulis, K.; Karamanis, D. (HNPS Advances in Nuclear Physics, 2019)
The analysis technique applied to the data from the FIC (Fast Induction Chamber) detector at the n_TOF facility is presented here. The measurements took place at the installation of CERN in Geneva. The detector was placed in front of the neutron beam for the determination of the neutron induced fission cross-section of various isotopes of the Th cycle. For the data acquisition, several fADC (flash Analog to Digital Converter) channels were used. This facilitated the detailed off-line analysis of data since all information was stored in the computer. The analysis of the data aimed at the discrimination of fission events. For this end we had to deal with three main issues: (1) The subtraction of the background, (2) the fitting of the pulses and (3) the automation of the process. The analysis pertaining to these issues will be further elucidated here.